Invasive fungal granuloma: a diagnostic challenge - Thaduri, Abhinav; Sreekanth, G.; Vishnuvardan, Dipin Kumar; Reddy, K. Sravani (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Invasive fungal rhinosinusitis is a rare and life-threatening with high mortality and morbidity. Granulomatous invasive fungal rhinosinusitis has a time course exceeding 12 weeks. This disease has been reported primarily in south of Asia, however, it is very rare. When the invasive fungal sinus infection presents in a form of a granuloma with unusual presentation then they pose a diagnostic challenge to medical professionals. We present a case series of 3 cases of invasive fungal granuloma with varied presentations, which posed as a challenge in diagnosing them. Chronic invasive fungal granuloma (CIFG) of the paranasal sinuses is seen in immunocompetent hosts, especially those that are in the 3rd and 4th decades of their lives. Involvement of maxillary sinus and orbit is common than the sphenoid sinus involvement. Routine H and E staining may prove inadequate. Special stains such as the GMS stain should be employed in the slightest doubt of a fungal aetiology. A team approach towards patients is paramount for early diagnosis and timely medical and surgical intervention.